2011
DOI: 10.3732/ajb.1000485
|View full text |Cite
|
Sign up to set email alerts
|

Resistance and tolerance to herbivory in Solidago altissima (Asteraceae): Genetic variability, costs, and selection for multiple traits

Abstract: Our study suggests that herbivores impose selection favoring increased tolerance and reduced resistance in goldenrods. In this environment, we expect that over time, resistant genets will decrease in frequency. Despite strong selection pressures, the evolution of tolerance in this environment may be constrained by the low broad-sense heritability in tolerance traits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
30
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(34 citation statements)
references
References 80 publications
2
30
2
Order By: Relevance
“…Various greenhouse and common-garden studies have revealed considerable genotypic variability in goldenrod resistance to insect herbivore attack (e.g., Maddox and Root 1987, McCrea and Abrahamson 1987. In the common-garden experiment, we did not find a signifi-cant effect of population of origin on genet resistance levels (Hakes and Cronin 2011b); however, we cannot reject the possibility that carryover effects within source populations inflated the variability seen among genets in resistance levels, and were subsequently lost in the present experiment. Of the 103 goldenrod genotypes used in the common-garden study, the 14 most different were used in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…Various greenhouse and common-garden studies have revealed considerable genotypic variability in goldenrod resistance to insect herbivore attack (e.g., Maddox and Root 1987, McCrea and Abrahamson 1987. In the common-garden experiment, we did not find a signifi-cant effect of population of origin on genet resistance levels (Hakes and Cronin 2011b); however, we cannot reject the possibility that carryover effects within source populations inflated the variability seen among genets in resistance levels, and were subsequently lost in the present experiment. Of the 103 goldenrod genotypes used in the common-garden study, the 14 most different were used in this study.…”
Section: Discussioncontrasting
confidence: 69%
“…It is even possible that low attack rates on S. gigantea reflect the evolution of increased resistance after G. gallaesolidaginis's host shift-and if resistance and tolerance trade off (Fornoni et al 2004;Núñez-Farfán et al 2007;Agrawal 2011; but see Jokela et al 2000) then a response to selection in resistance might pre-empt a response in tolerance. We have not measured resistance to G. gallaesolidaginis by S. altissima/gigantea, although Hakes and Cronin (2011) found selection against resistance to leaf-chewing herbivores in S. altissima (and no evidence for resistance-tolerance tradeoffs). Finally, the strength of selection on G. gallaesolidaginis virulence will depend on how much its impact on Solidago is mediated by its sequestration of plant resources into gall and insect tissues, versus by incidental damage to young leaves, meristems, and vascular tissue during gall formation.…”
Section: Discussionmentioning
confidence: 73%
“…Hakes and Cronin (2011) detected significant selection on S. altissima for increased tolerance to leaf-chewing herbivores, but measured very low heritability for tolerance and suggested this as a constraint on the evolution of tolerance. It is, however, unknown how tolerance of leaf-chewing relates to tolerance of gallmaking.…”
Section: Discussionmentioning
confidence: 91%
See 2 more Smart Citations